Effect of diet on the measurement of liver elasticity by real-time shear wave elastography in normal subjects - DING,Jin (2022)
Abstract To evaluate the liver stiffness measurement (LSM) of normal people before and after diet using real-time shear wave elastography (SWE), and to explore the effect of diet on liver elasticity. Fifty-four healthy volunteers were selected and 480 mL of a standard diet containing 391 kcal were administrated. The LSM before diet and at 30 minutes after diet was significantly higher than baseline LSM. The LSM at 60 minutes after diet was significantly higher than that before diet. The LSM at 120 minutes after diet was significantly less than that before diet. 75% of the volunteers reached the peak of liver stiffness at 30 minutes or 60 minutes after diet. The LSM increased by more than 20% in 31% subjects, increased by less than 20% in 48%, and remained or decreased in 21%. The blood flow volume of portal vein was 692.02 ± 130.69 mL/min before diet, and it reached the maximum value of 776.41 ± 151.45 mL/min at 30 min after diet. Diet could affect the Young’s modulus measurement of liver. In order to avoid the effect, it is suggested to use real-time shear wave elastic imaging to measure the Young's modulus of liver on an empty stomach.